THE ROLE OF TECHNOLOGY IN ADDRESSING THE WASTE EMERGENCY IN INDONESIA: A SOCIOLOGICAL STUDY OF DIGITAL WASTE BANK INNOVATION IN URBAN AREAS - Halim, Paisal; Badruddin, Syamsiah; P, Suci Ayu Kurniah; Damayanti, Dian (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The waste management crisis in Indonesia, particularly in urban areas, has spurred the emergence of various digital technology-based innovations, including digital waste bank applications such as eRecycle, Octopus, and Rekosistem. This study aims to analyze the role of these technologies in changing community participation patterns and their impact on community social dynamics. The research employed a qualitative approach using in-depth interviews, participant observation, and document study in three major cities : Jakarta, Makassar, and Surabaya. Findings indicate that economic incentives were the initial motivation for app use, but ecological awareness grew with continued participation. Technology also plays a role in shaping new forms of social capital through system transparency, participatory reporting, and strengthening community networks. However, there is a transformation from collective social interaction patterns to more individualistic digital participation. In addition, digital literacy barriers, limited access to technology, and social stigma against waste sorting activities remain serious challenges in creating inclusive engagement. The conclusion of this study confirms that the success of digital waste bank applications is highly dependent on the integration between technological innovation and community-based social approaches. This study recommends the need for strategies to strengthen digital social capital, public education, and policies that guarantee fair access and participation in technology-based waste management.